Peran Pengendalian Internal Sebagai Mediasi Moralitas Individu Dalam Pencegahan Kecurangan (Fraud) - Setianingrum, Dika Wahyu Setianingrum; Setiawan, Ade Budi; Anwar, Saepul (Universitas Pahlawan Tuanku Tambusai, 2025)
ABSTRACT This study discusses the effect of individual morality on fraud prevention mediated by Internal Control at BPKP RI, which is an internal auditor in government. The data collection technique was carried out by snowball sampling where the researcher was assisted by BPKP RI public relations in distributing questionnaires. This study examines how the relationship between individual morale and fraud prevention and examines how the relationship between individual morale and fraud prevention is mediated by internal control. This study also provides recommendations regarding what factors should be studied first to support fraud prevention, in order to facilitate the accomplishment of organizational objectives. Individual morality is considered a key or factor in fraud prevention. In addition, good internal control is also considered to minimize fraud. Keywords: BPKP RI, Individual Morality, Internal Control, Fraud Prevention.